2024
DOI: 10.3390/nu16071030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Low-Calorie Dietary Intervention on Liver Health and Body Weight in Adults with Metabolic-Dysfunction Associated Steatotic Liver Disease (MASLD) and Overweight/Obesity: A Systematic Review and Meta-Analysis

Laurence J. Dobbie,
Jamie Burgess,
Azlinda Hamid
et al.

Abstract: Introduction: Metabolic-dysfunction Associated Steatotic Liver Disease (MASLD) is a common cause of chronic liver disease. This review assessed the efficacy of a Low-Calorie Diet (LCD) on liver health and body weight in people living with MASLD and obesity. Methods: The study was registered with PROSPERO (CRD42021296501), and a literature search was conducted using multiple databases. The key inclusion criteria were randomised controlled trials or cohort studies, obesity/overweight and MASLD. Two authors scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Low-calorie diets (LCD) may reduce body weight and liver fat content in both MASLD and obese subjects, improving liver enzyme levels. Furthermore, Mediterranean-style LCDs, especially green-Mediterranean variants, may independently lower intrahepatic lipid content (IHL) and ALT levels compared to other LCDs [ 88 ]. Further insights from dietary intervention trials involving MASLD subjects are crucial to better understanding the dynamics of the contributing factors over time and their potential to differentiate the disease, thus serving as a personalized precision nutrition tool.…”
Section: Discussionmentioning
confidence: 99%
“…Low-calorie diets (LCD) may reduce body weight and liver fat content in both MASLD and obese subjects, improving liver enzyme levels. Furthermore, Mediterranean-style LCDs, especially green-Mediterranean variants, may independently lower intrahepatic lipid content (IHL) and ALT levels compared to other LCDs [ 88 ]. Further insights from dietary intervention trials involving MASLD subjects are crucial to better understanding the dynamics of the contributing factors over time and their potential to differentiate the disease, thus serving as a personalized precision nutrition tool.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis highlighted the Mediterranean lowcalorie diet as a favourable dietary approach for individuals with MAFLD and obesity [59]. This dietary pattern was associated with improved liver enzyme profiles in MAFLD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This dietary pattern was associated with improved liver enzyme profiles in MAFLD patients. Additionally, it was suggested that it may contribute to a reduction in IFC and overall liver health [59]. However, despite both current responders and non-responders to IFC improvement exhibiting higher adherence to the MedDiet and lower calorie consumption, only the responder group demonstrated a significant increase in VO 2 max after the 2-year intervention period.…”
Section: Discussionmentioning
confidence: 99%